The impact of environmental serious game on pro-environmental behavior through environmental psychological ownership and environmental self-efficacy - Jinsong Chen; Miao He; Shengxiang She (Scientific Reports)
Abstract Environmental serious games, propelled by rapid information technology development, represent a novel intervention in the environmental sector. The study seeks to investigate how environmental serious games influence pro-environmental behavior while examining the mediating roles of environmental psychological ownership and environmental self-efficacy. Utilizing literature review and theoretical derivation, the study establishes a research framework and employs questionnaire surveys and field methods to analyze the relationships between environmental serious games, pro-environmental behavior, environmental psychological ownership, and environmental self-efficacy. The findings demonstrate that environmental serious games effectively enhance public awareness and participation in environmental protection efforts. Environmental psychological ownership and environmental self-efficacy serve as mediators between gaming experiences and environmental behaviors. More specifically, games enhance players’ sense of environmental psychological ownership and environmental self-efficacy, consequently promoting more active environmental behaviors. These findings hold significant implications for the design and promotion of environmental serious games. They reveal the significant potential of games in enhancing public awareness and facilitating environmental behaviors, providing new avenues for environmental protection. Additionally, the study underscores the critical roles of environmental psychological ownership and environmental self-efficacy in game interventions, offering a theoretical foundation and guidance for future game design and evaluation. Furthermore, the findings provide insights into areas such as environmental education, policy development, and public management practices.